2017
DOI: 10.2147/copd.s138304
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of COPD among Aboriginal peoples in Canada: a cross-sectional study

Abstract: BackgroundCOPD among Aboriginal peoples in Canada is a major public health concern. This study was conducted in order to determine the prevalence and association between certain risk factors and COPD among the 35-year-old or older Aboriginal peoples in Canada.MethodsThis is a cross-sectional study. It uses data from Statistics Canada’s Aboriginal Peoples Survey (APS), 2012. It consists of 8,117 self-identified Aboriginal peoples, aged 35 years old or older from all Canadian provinces and territories. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
3
15
1
4
Order By: Relevance
“…The prevalence of COPD among adults was also reported in other studies from different countries. In comparison to our result, some studies reported lower prevalence [6.0% in Peru [33], 6.8% in Canada [9], 6.6% in Egypt [31], 13.4% in Korea [34] and 14.2% in Portugal [35]] and some other studies reported higher prevalence (24% in Netherlands [36], 18.4% in Greece [37] and 21.8% in Russia [38]]. In fact, the prevalence of COPD is variable across countries and across different groups within countries [18].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The prevalence of COPD among adults was also reported in other studies from different countries. In comparison to our result, some studies reported lower prevalence [6.0% in Peru [33], 6.8% in Canada [9], 6.6% in Egypt [31], 13.4% in Korea [34] and 14.2% in Portugal [35]] and some other studies reported higher prevalence (24% in Netherlands [36], 18.4% in Greece [37] and 21.8% in Russia [38]]. In fact, the prevalence of COPD is variable across countries and across different groups within countries [18].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the prevalence of COPD in the smoker group (both former and current smoker) was found to be higher than that in the non smoker group. Similar findings were reported in several studies [1, 3, 7, 9, 41]. Cigarette smoking is the most common risk factor for COPD worldwide [3].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, a cross-sectional study among Aboriginal people assessed the risk factors associated with COPD. It was reported that individuals aged 55 and older were significantly associated with the risk of COPD [18]. We could find no other studies that focused on Aboriginal peoples with ACO.…”
Section: Discussionmentioning
confidence: 85%
“…A large population-based study of 8,028 individuals reported that low income and low quality of education were risk factors for asthma and COPD [29]. In a cross-sectional study that focused on the associated factors of COPD among Aboriginal peoples, the authors reported that Aboriginal peoples making less than the median income of $20,600 were at a higher risk to be associated with COPD [18].…”
Section: Discussionmentioning
confidence: 99%